System Approach and Design Models of PAI Learning: Pendekatan Sistem Dan Model-Model Desain Pembelajaran PAI - M. Sayyidul Abrori; Yanuar Wicaksono; Dika Tripitasari (Journal of Contemporary Islamic Education, 2021)
This article is focused on examining the systems approach and Pai's learning design models. Today teachers are required to be able to make appropriate learning plans according to the needs of students. The technique used is the result of documentation of existing reference sources and other written information. Analysis of research data using descriptive analysis, content analysis, and comparative analysis. The results of this discussion explain that the PAI learning system approach is a component that integrates with each other, functions cooperatively, and influences each other. In the PAI learning system approach, there are several planning components, namely: a. Establish PAI learning objectives, b. Determine the strategy for organizing the contents of Islamic Education lessons, c. Planning the roles of teachers and students in learning, d. Determine the PAI learning strategy, e. Determine the technique of evaluating the learning outcomes of Islamic Education. Meanwhile, the PAI learning model designs are: a. ASSURE learning design model, b. ADDIE learning design model, c. Kemp learning design model, d. PPSI learning design model, e. The Dick and Carey learning design model, f. The Briggs learning design model and examples in the form of management lesson plans are attached to the research results.